How lessons are taught: a case study of a linguistic approach to teacher's discourse - Muck, Kátia Eliane (2013)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente, Florianópolis, 2010